Genre-based analysis of travel guides: a study on Malaysia, Thailand and the Philippines - Alali, Bashar Abdulkareem; Mohamad Ali, Afiza; Mohamad Ali, Afida (Language Academy, Universiti Teknologi Malaysia, 2019)
The language of travel guides can help highlight the importance of modelling the mind of the readers and changing them from readers to actual clients. This paper reports a genre- based analysis study of a move-structure of online tourist travel guides of three Asian countries: Malaysia, Thailand and the Philippines. Kathpalia’s nine-move structure (1992) for advertising is adopted as a framework to analyse the selected travel guides using Atlas ti (a qualitative data analysis software). Data selection is based on the latest edition of Asian online travel guides. The main purposes of this study are to analyze the move structures, their strategies and communicative purposes, identify the prevalent move(s) in the selected travel guides, as well as to find out whether the selected travel guides have the same move structures. The findings of this study show that the travel guides have different quantity of moves. The prevalent moves in these three travel guides were also identified. Results highlight the diversity and strategies of moves in the online travel guides which are related to the nature of the country, perception and aims of the writer to promote or persuade readers. A brief discussion on these categories, and teaching implications follow these findings.